Effects of oil production on economic growth in Eurasian countries: Panel ARDL approach - Bildirici, Melike Elif; Kayikci, Fazil (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
This study aims at analyzing the relationship between oil production and economic growth in major oil exporting Eurasian countries; Azerbaijan, Kazakhstan, Russian Federation and Turkmenistan for 1993-2010 periods. Empirical results reveal that oil production and economic growth are cointegrated for these countries. Furthermore, there is positive bi-directional causality between oil production and economic growth both in the long run and in the short run which supports the policies about investing in energy infrastructure. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Growth; Cointegration; Causality; Oil production; ENERGY-CONSUMPTION; TIME-SERIES; TESTS; Thermodynamics; Energy & Fuels